Genome-wide DNA methylation profile implicates potential cartilage regeneration at the late stage of knee osteoarthritis. Issue 5 (May 2016) - Zhang, Y.; Fukui, N.; Yahata, M.; Katsuragawa, Y.; Tashiro, T.; Ikegawa, S.; Michael Lee, M.T.
Summary: Objective: The aim of this work was to characterize the genome-wide DNA methylation profile of cartilage from three regions of tibial plateau isolated from patients with primary knee osteoarthritis (OA), providing the first DNA methylation study that reflects OA progression. Methods: The unique model system was used to section three regions of tibial plateau: the outer lateral tibial plateau (oLT), the inner lateral tibial plateau (iLT) and the inner medial tibial plateau (iMT) regions which represented the early, intermediate and late stages of OA, respectively. Genome-wide DNA methylation profile was examined using Illumina Infinium HumanMethylation450 BeadChip array. Comparisons of the iLT/oLT and iMT/oLT groups were carried out to identify differentially methylated (DM) probes (DMPs) associated with OA progression. DM genes were analyzed to identify the gene ontologies (GO), pathways, upstream regulators and networks. Results: No significant DMPs were identified in iLT/oLT group, while 519 DMPs were identified in iMT/oLT group. Over half of them (68.2%) were hypo-methylated and enriched in enhancers and OpenSea. Upstream regulator analysis identified many microRNAs. DM genes were enriched in transcription factors, especially homeobox genes and in Wnt/β-catenin signaling pathway. These genes also showed changes in expression when analyzed with expression profiles generated from previous studies. Conclusion: Our data suggested the changes in DNA methylation occurred at the late stage of OA. Pathways and networks enriched in identified DM genes highlighted potential etiologic mechanism and implicated the potential cartilage regeneration in the late stage of knee OA.